Lung on a Chip for Drug Screening and Design - Kızılkurtlu, Ahmet A.; Polat, Tuğçe; Aydın, Gül Banu; Akpek, Ali (Current Pharmaceutical Design, 2018)
Lung-on-a-chip is a micro device that combines the techniques of bioengineering, microbiology, polymer science and microfluidics disciplines in order to mimic physicochemical features and microenvironments, multicellular constructions, cell-cell interfaces of a human lung. Specifically, most novel lung on a chip designs consist of two micro-channeled outer parts, flexible and porous Polydimethylsiloxane (PDMS) membrane to create separation of air-blood chamber and subsidiary vacuum channels which enable stretching of the PDMS membrane to mimic movement mechanisms of the lung. Therefore, studies aim to emulate both tissue and organ functionality since it shall be creating great potential for advancing the studies about drug discovery, disease etiology and organ physiology compared with 2D (two dimensional) and 3D (three dimensional) cell culture models and current organoids. In this study, history of researches on lung anatomy and physiology, techniques of recreating lung functionality such as cell cultures in 2D and 3D models, organoids were covered and finally most advanced and recent state of the art technology product lung-on-a-chips’ construction steps, advantages compared with other techniques, usage in lung modeling and diseases, present and future offers were analyzed in detail.
Keywords: Lung-on-a-chip